Field thermo acclimation increases the resilience of Posidonia oceanica seedlings to marine heat waves. (November 2022) - Stipcich, Patrizia; Pansini, Arianna; Beca-Carretero, Pedro; Stengel, Dagmar B.; Ceccherelli, Giulia
Abstract: Acclimation is a response that results from chronic exposure of an individual to a new environment. This study aimed to investigate whether the thermal environment affects the early development of the seagrass Posidonia oceanica, and whether the effects of a field-simulated Marine Heat Wave (MHW) on seedlings change depending on acclimation. The experiment was done in the field using a crossed design of Acclimation (acclimated vs unacclimated) and MHW (present vs absent) factors. Acclimation has initially constrained the development of P. oceanica seedlings, but then it increased their resilience to the MHW, under both a morphological and biochemical (fatty acid saturation) level. This treatment could be considered in P. oceanica restoration projects in a climate change-impaired sea, by purposely inducing an increased resistance to heat before transplants. Highlights: Acclimation induces an individual adjustment to a new environment. Warming initially stressed P. oceanica seedlings by constraining their development. Acclimation increased the seedling resilience to the field-simulated MHW. The FA C18:3 n-3/C16:0 was proposed as a new biomarker of thermal stress. Restoration projects may consider inducing a resistance to heat before transplants.